The effects of early childhood probiotic intake on the association between prenatal micronutrient supplementation and neurobehavioral development in preschool children: a four-way decomposition analysis - Ding, Liwen; Zhang, Maolin; Strodl, Esben; Yin, Xiaona; Wen, Guomin; Sun, Dengli; Xian, Danxia; Zhao, Yafen; Zheng, Yuxing; Liu, Feitong; Hu, Ruibiao; Zhao, Lingling; et al. (Frontiers in Nutrition, 2025)
BackgroundNeurobehavioral developmental disorder (NDD) significantly impact children’s long-term wellbeing and contribute to global disease burden. While prenatal micronutrient supplementation has shown promise in improving fetal neurodevelopment, its association with offspring’s neurobehavioral outcomes remains controversial, and the potential effect of early childhood probiotic intake on this association is still underexplored. This study aimed to evaluate the association between prenatal micronutrient supplementation and neurobehavioral development in preschool children, and to explore and quantify the effect of early childhood probiotic intake on this association.MethodsWe included 15,636 mother–child dyads in Shenzhen, China, in 2022. Mothers provided information on prenatal micronutrient supplementation (calcium, folic acid, iron, and multivitamins) and early childhood probiotic intake through a structured questionnaire. Neurobehavioral development was assessed using the Ages and Stages Questionnaire (ASQ-3). Logistic regression was used to examine the association between prenatal micronutrient supplementation and NDD across crude, adjusted, and full-inclusion models. The effect of early childhood probiotic intake on the association between prenatal micronutrient supplementation and NDD was evaluated through four-way decomposition analysis and quantified using counterfactual attribution under three scenarios.ResultsAmong the participants, 11.7% were identified with NDD. Prenatal multivitamin supplementation was significantly associated with a reduced risk of NDD (OR = 0.73, 95% CI = 0.66–0.81). Early childhood probiotic intake was associated with an enhanced protective effect (Total EOR = −0.33, 95% CI = −0.54 to −0.12), with 48% of the effect attributable to interactions. Early childhood probiotic intake could prevent an additional 73 NDD cases (a 59% increase), particularly benefiting the gross motor, fine motor and personal-social domains.ConclusionPrenatal multivitamin supplementation has a protective effect against NDD in preschool children, and early childhood probiotic intake is associated with an enhancement of this protective effect. These findings underscore the potential effect of early-life dietary supplements for NDD prevention. Further studies are recommended to confirm these effects and explore underlying mechanisms.